2008
DOI: 10.1002/jctb.2067
|View full text |Cite
|
Sign up to set email alerts
|

Removal of DDT from aqueous solutions using mesoporous silica materials

Abstract: BACKGROUND: There are few reports about adsorbents for the effective removal of large-molecule pesticides such as DDT (1,1,1-trichloro-2,2 bis(p-chlorophenyl)ethane). Some mesoporous silica materials and their modified derivatives might serve as good adsorbents for these large organic molecules because of their large pore diameter and special pore structures. In this work, the adsorption processes of DDT in aqueous solutions were investigated using different mesoporous silica materials, including HMS, MCM-41, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
(26 reference statements)
4
27
0
Order By: Relevance
“…Compared with pure SBA-15, Fe-SBA-15 samples have smaller pore diameters although their surface areas were much larger than that of SBA-15 (Table 1). The adsorption results indicate that the pore diameter of mesoporous material might have a significant effect on its adsorption ability for large organic molecules, which was also proved by Tian's research (Tian et al, 2009b). We also found that DDE adsorption efficiency on Fe-SBA-15 had increased when compared with pure SBA-15, which might be related not only with the different DDE molecule structure from DDD and DDT, but also with the alkaline of Fe-SBA-15.…”
Section: Ddts Adsorptionsupporting
confidence: 70%
See 2 more Smart Citations
“…Compared with pure SBA-15, Fe-SBA-15 samples have smaller pore diameters although their surface areas were much larger than that of SBA-15 (Table 1). The adsorption results indicate that the pore diameter of mesoporous material might have a significant effect on its adsorption ability for large organic molecules, which was also proved by Tian's research (Tian et al, 2009b). We also found that DDE adsorption efficiency on Fe-SBA-15 had increased when compared with pure SBA-15, which might be related not only with the different DDE molecule structure from DDD and DDT, but also with the alkaline of Fe-SBA-15.…”
Section: Ddts Adsorptionsupporting
confidence: 70%
“…We previously reported that mesoporous silica SBA-15 could be used as effective adsorbent for the removal of DDT from aqueous solutions due to its high surface area and large pore size (Tian et al, 2009b). In which the thermal treatment of the DDT-adsorbed adsorbents was carried out at 450°C in air, which is much lower than the traditional incineration technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four mesoporous silicas, including SBA-15, MCM-41, MCM-48 and KIT-6 were synthesized according to the procedures described in the literature [25][26][27][28]. The nonionic Pluronic P123 (EO 20 PO 70 EO 20 ) was used as a template for the synthesis of SBA-15 and KIT-6, whereas the cetyltrimethyammonium bromide (CTAB) was used for MCM-41 and MCM-48.…”
Section: Preparation Of Mesoporous Silicasmentioning
confidence: 99%
“…Mesoporous silica is promising material to be applicable in the supporting materials for catalyst, water purification, chemical exchange system, and biosensor owing to its properties as high chemical and thermal resistant, inert, as well as non-toxic. Moreover, the modifications of mesoporous silica with nanometallic particles and the organic functions have been studied for catalyst, electrical and optical devices, imaging and sensing sensors, and biomedical applications [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%